PERAN GURU PENDIDIKAN AGAMA KRISTEN SEBAGAI KONSELOR BAGI PERUBAHAN PERILAKU REMAJA KELAS X-XI DI SMA NEGERI 48 JAKARTA TIMUR - Diana Rotua Silaban (Regula Fidei: Jurnal Pendidikan Agama Kristen, 2018)
This research was conducted to see the role of Christian Religious Education Teacher As Counselor for Change of Youth Behavior in SMA Negeri 48 Pinang Ranti Class X-XI. The method used in this research is qualitative method. This is done by collecting primary data through observation, interviews, and documentation. The data were obtained through teachers of PAK study and some students of SMA Negeri 48 Pinang Ranti. Through the results of research proves that teachers of Christian Religious Education (PAK) is a useful figure helping others to grow in the knowledge of Christian faith and experience of believing in person. Teachers not only task to convey knowledge to students, but also have other role, that is role as counselor. Teachers as counselors will help every student who is in trouble, and accompany children to find a solution to the problems faced so they can get out of the problems that are facing. Abstrak: Penelitian ini dilakukan untuk melihat seberapa besar Peran Guru Pendidikan Agama Kristen Sebagai Konselor Bagi Perubahan Perilaku Remaja di SMA Negeri 48 Pinang Ranti Kelas X-XI. Metode yang dipakai dalam penelitian ini adalah metode kualitatif. Hal ini dilakukan dengan pengumpulan data primer melalui observasi, wawancara, dan dokumentasi. Data diperoleh melalui guru bidang studi PAK dan beberapa peserta didik SMA Negeri 48 Pinang Ranti. Melalui hasil penelitian membuktikan bahwa guru Pendidikan Agama Kristen (PAK) adalah sosok yang berguna menolong orang lain untuk bertumbuh dalam pengetahuan.